2010
DOI: 10.1137/09075740x
|View full text |Cite
|
Sign up to set email alerts
|

Parallel High-Order Integrators

Abstract: Abstract. In this work we discuss a class of defect correction methods which is easily adapted to create parallel time integrators for multi-core architectures and is ideally suited for developing methods which can be order adaptive in time. The method is based on Integral Deferred Correction (IDC), which was itself motivated by Spectral Deferred Correction by Dutt, Greengard and Rokhlin (BIT-2000).The method presented here is a revised formulation of explicit IDC, dubbed Revisionist IDC, which can achieve p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 31 publications
0
91
0
Order By: Relevance
“…The integral deferred correction methods we have already seen in Subsection 4.4 in the context of PFASST can also be used to create naturally small scale parallelism [14]:…”
Section: Christlieb Macdonald and Ong 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…The integral deferred correction methods we have already seen in Subsection 4.4 in the context of PFASST can also be used to create naturally small scale parallelism [14]:…”
Section: Christlieb Macdonald and Ong 2010mentioning
confidence: 99%
“…18 Classical application of integral deferred correction, picture taken from [14] deferred correction the quadrature formula for (33) at time t j,m+1 , using quadrature points at time t j,0 ,t j,1 , . .…”
Section: Christlieb Macdonald and Ong 2010mentioning
confidence: 99%
“…In the relatively recent field of time parallelization, there are four main algorithmic techniques that have been investigated: methods based on multiple shooting (Chartier and Philippe 1993), like the parareal algorithm (Lions et al 2001) for which a detailed convergence analysis can be found in Gander and Vandewalle (2007) for the linear case and in Gander and Hairer (2008) for the nonlinear case; methods based on space-time decomposition, like classical Schwarz waveform relaxation (Bjørhus 1995;Gander and Stuart 1998;Giladi and Keller 2002) and optimized variants (Bennequin et al 2009;Halpern 2005, 2007;, and Dirichlet-Neumann and Neumann-Neumann waveform relaxation (Gander et al 2016b;Kwok 2014;Mandal 2014); space-time multigrid methods (Emmett and Minion 2012;Gander and Neumüller 2016;Hackbusch 1984;Horton and Vandewalle 1995); and direct time parallelization methods like tensor product methods (Maday and Rønquist 2008), RIDC (Christlieb et al 2010), and ParaExp (Gander and Güttel 2013); for an up to date overview and a historical perspective of these approaches, see Gander (2015). This is because modern supercomputers have now so many processors that often space parallelization strategies for evolution problems saturate before all available processors can be used.…”
Section: Introductionmentioning
confidence: 99%
“…We are not aware of any other studies that investigate SDC integration methods in conjunction with particle-based spatial solvers aside from a small, one-dimensional Nbody example in [2] for Revisionist Integral Deferred Corrections (RIDC).…”
Section: Introductionmentioning
confidence: 99%